Serving Their Communities: An Analysis of Australian Public Library Mission Statements. Issue 2 (17th February 2022) - Hider, Philip; Garner, Jane; Wakeling, Simon; Jamali, Hamid R.
Abstract: To understand the roles that Australian public libraries are aiming to play in their communities, mission statements from a sample of fifty public library networks were extracted from their corporate documents and subjected to both quantitative and qualitative content analysis. The five broader roles most commonly articulated were to facilitate learning and discovery, to increase social connectedness, to provide spaces and places, to provide access to information and resources, and to facilitate inclusion and celebrate diversity. Overall, the mission of Australian public libraries focuses more on learning and community building than on their traditional function of information access provision.